Amplifying Agroecological Farmer Lighthouses in Contested Territories: Navigating Historical Conditions and Forming New Clusters in Japan - McGreevy, Steven R.; Tamura, Norie; Kobayashi, Mai; Zollet, Simona; Hitaka, Kazumasa; Nicholls, Clara I.; Altieri, Miguel A. (Frontiers in Sustainable Food Systems, 2021)
Individual agroecological farms can act as lighthouses to amplify the uptake of agroecological principles and practices by other farmers. Amplification is critical for the upscaling of agroecological production and socio-political projects emphasizing farmer sovereignty and solidarity. However, territories are contested spaces with historical, social, cultural, and economic contexts that can present challenges to the effectiveness of farmer lighthouses in catalyzing localized agrarian change. We explore these amplification dynamics through fieldwork in a particular region of Japan employing interviews and data derived from an assessment of nine farms using ten amplification indicators. The indicators include social organization, participation in networks, community leadership, and degrees of dependency on policies or markets among others, as well as degree of adoption of on-farm agroecological practices, all of which capture farmer lighthouses' potential to amplify territorial upscaling. At the same time, we trace the historical development of a previous generation of Japanese farmer lighthouses practicing organic agriculture in alignment with agroecological principles that experienced, to varying degrees, push-back, co-option, and successful territorialization in rural communities. We find that many of the same social and cultural territorial dynamics are still influential today and affecting the amplifying effect of agroecological farmer lighthouses, but also find examples of new clustering around lighthouses that take advantage of both the historical vestiges of the previous generation's efforts as well as contemporary shifts in practice and agrarian orientation. This research calls for a detailed dissection of the dynamic and contrasting processes of agroecological territorialization and the ways in which diverse contexts shape agroecological upscaling.